A DIFFERENT ANGLE: EXPLORING ENVIRONMENTAL INFLUENCES ON THE FARMER-HERDER CONFLICT IN BENUE STATE - Ajayi, Michael Oluwatosin; Eze, ohn Chinedu (Research Journal of Economics and Sustainable Development, 2024)
Resource conflict between farmers and herdsmen has been a major issue in Benue State, Nigeria. This study aimed to identify the determinants of resource conflict between these two groups and to determine the prevalence of resource conflict factors in Benue State. A field survey was carried out, with 382 residents of Benue State participating in the study through questionnaires, interviews, and focus group discussions. The study revealed that human factors, such as economic, cultural, and population, were the major drivers of resource conflict between farmers and herders, rather than environmental factors like erosion, flood, and drought. Although environmental factors were agreed upon by both farmers and herders to have some influence on resource conflict, they differed in their perceptions of human factors, such as socioeconomic, socio-cultural, and political factors, as major drivers. The findings of this research highlight the need for measures to address these human factors in order to reduce resource conflict in Benue State. This study recommends promoting skill acquisition and job creation among youth to boost the economy of the state, reduce conflict, and promote peaceful coexistence.